2021
DOI: 10.3390/ma14216540
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Flexible Electronic Textile for Heating Application: A Critical Review

Abstract: Intelligent textiles are predicted to see a ‘surprising’ development in the future. The consequence of this revived interest has been the growth of industrial goods and the improvement of innovative methods for the incorporation of electrical features into textiles materials. Conductive textiles comprise conductive fibres, yarns, fabrics, and finished goods produced using them. Present perspectives to manufacture electrically conductive threads containing conductive substrates, metal wires, metallic yarns, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 165 publications
0
19
0
Order By: Relevance
“…Certain resistivity and conductivity values are needed to obtain a heating effect according to Joule's Law. For the generation of active heat in a fabric, the coating of a paste made of an active material with good conductivity mixed with an insulating polymer is one of the methodologies [1]. In this study, the heating effect of the coated samples was investigated by applying 12 V, in particular to be able to use them in automotive applications.…”
Section: Joule Heatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain resistivity and conductivity values are needed to obtain a heating effect according to Joule's Law. For the generation of active heat in a fabric, the coating of a paste made of an active material with good conductivity mixed with an insulating polymer is one of the methodologies [1]. In this study, the heating effect of the coated samples was investigated by applying 12 V, in particular to be able to use them in automotive applications.…”
Section: Joule Heatingmentioning
confidence: 99%
“…Even though textiles have historically mainly been used for clothing purposes, the advancement of technology has opened up their use for various other applications. Textile materials possess high electrical resistance, low electrical conductivity, and low thermal conductivity in their pristine state [1]. Developments in nanotechnology have given the opportunity of introducing new functionalities to textiles, endowing the production of smart and intelligent textiles [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical review by Repon et al [17] indicated the importance of the recent advances in conductive textiles comprising conductive fibers, yarns, and fabrics, and the finished goods produced using them. These electrically conductive threads contain conductive substrates, metal wires, metallic yarns, nanomaterial additives, and intrinsically conductive polymers.…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%
“…The electric heating functionality can be realized in a textile fabric by means of coating, lamination, printing, and integration . In previous research, metal-, conductive polymer-, and carbon-based materials were used to develop the electrical-based heating textile. It has been found that textile substrates were coated with conductive polymers such as polypyrrole (PPy), polyethylene dioxophene thiophene (PEDOT), graphene oxide (GO), polyaniline, and polythiophene for the fabrication of the heating fabric/pad. Although the heating textiles coated with a conductive polymer exhibited high conductivity, the comfortability of the fabric suffers due to increased rigidity and impermeability.…”
Section: Introductionmentioning
confidence: 99%